2014
DOI: 10.1371/journal.pone.0107377
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mucosal Responses after Intramuscular Immunization with Integrase Defective Lentiviral Vector

Abstract: Many infectious agents infiltrate the host at the mucosal surfaces and then spread systemically. This implies that an ideal vaccine should induce protective immune responses both at systemic and mucosal sites to counteract invasive mucosal pathogens. We evaluated the in vivo systemic and mucosal antigen-specific immune response induced in mice by intramuscular administration of an integrase defective lentiviral vector (IDLV) carrying the ovalbumin (OVA) transgene as a model antigen (IDLV-OVA), either alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…In the case of chimeric bovine papillomavirus virus-like particles incorporating sequence from human immunodeficiency virus-1 gp120, the vaginal IgA induction was higher following IM administration as compared to intravaginal administration [ 28 ]. Intramuscular administration of integrase-defective lentiviral vector carrying ovalbumin gene followed by sublingual ovalbumin administration was reported to induce persistent vaginal IgA immune responses [ 29 ]. A recent study reported that SL immunization of female human volunteers with Gardasil induced 38-fold lower serum IgG levels and 2-fold lower cervical/vaginal IgG levels than IM immunization [ 30 ], highlighting the importance of the delivery system for SL immunization.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of chimeric bovine papillomavirus virus-like particles incorporating sequence from human immunodeficiency virus-1 gp120, the vaginal IgA induction was higher following IM administration as compared to intravaginal administration [ 28 ]. Intramuscular administration of integrase-defective lentiviral vector carrying ovalbumin gene followed by sublingual ovalbumin administration was reported to induce persistent vaginal IgA immune responses [ 29 ]. A recent study reported that SL immunization of female human volunteers with Gardasil induced 38-fold lower serum IgG levels and 2-fold lower cervical/vaginal IgG levels than IM immunization [ 30 ], highlighting the importance of the delivery system for SL immunization.…”
Section: Discussionmentioning
confidence: 99%
“…have successfully employed IDLVs in mouse models as gene replacement therapies for degenerative retinal disease and hemophilia B, respectively. Furthermore, the efficacy of IDLVs in cancer immunotherapy and as a means of inducing protective immune responses to human pathogens has been characterized in different experimental settings 38, 39, 40. A growing body of literature describes IDLVs carrying zinc-finger nucleases as an effective means of gene editing for clinical and basic science applications28, 30, 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…18 Mice immunized intranasally with IDLV expressing the influenza virus nucleoprotein (Flu-NP) were protected against Influenza virus challenge 19 and therapeutic vaccination with IDLV expressing the human papillomavirus 16 E7 protein (HPV-E7) as a tumor antigen resulted in the eradication of TC-1-derived tumor in tumor-bearing mice. 20 Antigen presentation persists for at least 30 days following IDLV immunization, 21 suggesting that IDLV provides prolonged expression of the encoded antigen, a desirable feature for any vaccine to achieve sustained protection over time.…”
Section: Introductionmentioning
confidence: 99%